Early Childhood Administrators’ Attitudes Towards Inclusive Education: A Systematic Review - Serife Balikci; Emrah Gulboy; Salih Rakap (Education Sciences, 2025)
Inclusive education in early childhood is pivotal for fostering equitable learning opportunities and promoting diversity from a young age. Administrators play a key role in implementing inclusive practices effectively within educational settings. This systematic review synthesizes the attitudes of early childhood education administrators towards inclusion, examining how these attitudes influence the successful integration of inclusive practices and identifying the factors that impact these perspectives. A total of 18 studies were identified through a systematic search procedure and included in this review. The results reveal a generally positive attitude towards inclusion among administrators, tempered by notable challenges, such as insufficient training and inadequate resources. These challenges align with variations in administrators’ readiness to implement inclusive practices. This review also highlights variability in how administrators perceive their roles in inclusive education, ranging from instructional leaders to supportive facilitators. Although some studies identified influencing factors, such as gender, education level, and school location, these were more strongly associated with overall attitudes towards inclusion rather than role perception specifically. The implications for policy involve strengthening resource allocation and training for administrators to support inclusive practices effectively. For practice, there is a need to develop robust support structures and targeted professional development programs that address the specific needs of administrators in fostering inclusivity. Future research should expand to include diverse global perspectives and explore the nuances of administrative roles in different cultural and educational settings.